The Role of Regulatory T Cell in Nontypeable Haemophilus influenzae-Induced Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Xuewa Guan; Yanjiao Lu; Guoqiang Wang; Peter Gibson; Fang Chen; Keyong Fang; Ziyan Wang; Zhiqiang Pang; Yingqiao Guo; Junying Lu; Yuze Yuan; Nan Ran; et al. (Mediators of Inflammation)
Chronic obstructive pulmonary disease (COPD) is associated with irreversible persistent airflow limitation and enhanced inflammation. The episodes of acute exacerbation (AECOPD) largely depend on the colonized pathogens such as nontypeable Haemophilus influenzae (NTHi), one of the most commonly isolated bacteria. Regulatory T cells (Tregs) are critical in controlling inflammatory immune responses and maintaining tolerance; however, their role in AECOPD is poorly understood. In this study, we hypothesized a regulatory role of Tregs, as NTHi participated in the progress of COPD. Immunological pathogenesis was investigated in a murine COPD model induced by cigarette smoke (CS). NTHi was administrated through intratracheal instillation for an acute exacerbation. Weight loss and lung function decline were observed in smoke-exposed mice. Mice in experimental groups exhibited serious inflammatory responses via histological and cytokine assessment. Expression levels of Tregs and Th17 cells with specific cytokines TGF-β1 and IL-17 were detected to assess the balance of pro-/anti-inflammatory influence partially. Our findings suggested an anti-inflammatory activity of Tregs in CS-induced model. But this activity was suppressed after NTHi administration. Collectively, these data suggested that NTHi might play a necessary role in downregulating Foxp3 to impair the function of Tregs, helping development into AECOPD.